Uma abordagem para visualização espaço-temporal - Vieira, Ana Paula dos Santos Braatz (2018)
Analyzing and understanding spatial data that varies over time is a complex task. Usually, the data is arranged in a tabular or text form. We developed the ST-Vis (SpatioTemporal Visualization) tool to provide a visual representation of spatiotemporal data, which must help users to understand the temporal variation in a region when combining the parallel coordinate graph with a geographical map, the temporal texture, and a table. The temporal texture results in a representation of colors for the variation of the Normalized Difference Vegetation Index (NDVI), each texture cell refers to a period to be analyzed. ST-Vis provides a simultaneous spatiotemporal representation of data, and the visualizations interact with each through animations. We evaluated the ST-Vis tool through a conversation with some domain specialists in the area, and through a form applied to some experts in the field, students and teachers in the area of agribusiness, computing, and other areas. It has been found that ST-Vis assists users in understanding spatiotemporal data through generated visualizations